Preparation method of two-dimensional layered vermiculite mineral-based nano confinement material and application of two-dimensional layered vermiculite mineral-based nano confinement material in catalytic degradation of antibiotic pollutants

By preparing two-dimensional layered vermiculite mineral-based nano-domain material as a catalyst, the problem of easy oxidation and agglomeration of catalysts in the prior art is solved, and efficient degradation of antibiotic pollutants and water quality purification is achieved.

CN119425731APending Publication Date: 2025-02-14HEFEI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411571514.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when catalyzed degradation of antibiotic pollutants, the catalyst is prone to oxidation and agglomeration, resulting in low catalytic efficiency, and the treated water may have color, which has limitations.

Method used

Two-dimensional layered vermiculite mineral-based nano-domain confined materials are used as catalysts, and prepared by calcining and ion exchange steps, combined with hydrogen reduction and calcining and autoclave technology to generate nano-domain confined catalysts with high activity.

Benefits of technology

The catalytic reaction activity of the catalyst is improved, and the efficient degradation of antibiotic pollutants is achieved. The antibiotic degradation rate in the treated water can reach 100%, the TOC removal rate reaches more than 70%, and color pollution is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425731A_ABST
    Figure CN119425731A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a two-dimensional layered vermiculite mineral-based nano confinement material and application of the two-dimensional layered vermiculite mineral-based nano confinement material in catalytic degradation of antibiotic pollutants. According to the method, vermiculite minerals, rhodochrosite minerals, tourmaline minerals and sulfur minerals serve as raw materials, the two-dimensional layered vermiculite mineral-based nano confinement mineral material is prepared to serve as a catalyst, persulfate is activated to catalytically degrade antibiotics, the problem of agglomeration of the nano mineral material can be effectively solved, and high degradation efficiency and mineralization rate are achieved. The catalyst is in a nanoscale, and provides a constrained environment for a catalytic reaction system, so that accurate regulation and control of catalytic performance are realized, the efficiency of catalytic reaction is improved, and the problem of low efficiency of catalytic degradation of antibiotics by a current commercially available catalyst is solved. The preparation method is simple, the raw materials are cheap and easy to obtain, and the preparation method is green and environment-friendly and can be industrially applied on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the fields of mineral processing, degradation of antibiotic pollutants, and specifically relates to a preparation method of a two-dimensional layered vermiculite mineral-based nano-confined material and its application in catalytic degradation of antibiotic pollutants. Background Art

[0002] The discharge of medical sewage is more complicated than that of general domestic sewage. In addition to domestic sewage components, it also contains antibiotics. If not effectively treated, these sewage will seriously pollute the environment. Therefore, deep treatment is necessary to ensure that the discharge meets the standards. Antibiotics refer to a class of important secondary metabolites produced by microorganisms or higher animals and plants in their life processes that have anti-pathogen or other biological activities and can interfere with the developmental functions of cells. The use of antibiotics may cause pathogenic microorganisms to develop drug resistance, thereby increasing the dose of antibiotics required to effectively kill bacteria. Long-term discharge of low-dose antibiotics into the environment will enhance the drug resistance of sensitive bacteria, and drug-resistant genes may also expand and evolve in the environment, which poses a potential threat to the ecological environment and human health, and may have certain toxicity to other organisms.

[0003] At present, the methods for purifying antibiotics are mainly divided into physical methods, chemical methods and biological methods. Among them, advanced oxidation technology has become a typical representative of chemical methods due to its strong oxidizing properties. Typical AOPs generate hydroxyl radicals by using ozone, hydrogen peroxide, etc. under specific conditions (such as sound, light, heat, and electricity). Its strong oxidizing property (2.8V, second only to fluorine's 2.87V) enables it to react non-selectively with antibiotics and eventually degrade into carbon dioxide and water. In contrast, sulfate radicals (SO4· - ) has a higher redox potential, based on the activation of persulfate to generate SO4· - The advanced oxidation method shows great potential. SO4· - The standard potential under different conditions can reach 2.5-3.1V, even higher than OH, and its application range is wider. Persulfate has the advantages of stable structure, easy storage and transportation, high water solubility and low cost, so it has been widely used in the degradation of antibiotic pollutants.

[0004] The advanced oxidation process using a combination of iron salts and persulfate has the advantages of fast catalytic reaction speed and high treatment efficiency, with a degradation rate of up to 90%. However, this catalyst will cause Fe 2+ As the concentration increases, the treated water may be colored, so additional alkali needs to be added to precipitate Fe 2+ ions and adjust the pH value of the solution, which has great limitations in practical applications. 2+ The existence of Fe is affected by the solution environment, and nano-zero-valent iron composites are gradually used to replace Fe2+ Its advantages in activating persulfate are gradually emerging. However, there are many problems in the practical application of nano-zero-valent iron, such as easy oxidation and easy agglomeration, which limits its large-scale application.

[0005] In order to solve the above problems, our team used iron salt and sulfur salt as raw materials to prepare sulfide nano zero-valent iron composite materials by liquid phase reduction method. However, the composite materials still show agglomeration phenomenon, which cannot fundamentally solve the shortcomings of easy oxidation and passivation of sulfide nano zero-valent iron composite materials. This is because the surface active energy between sulfide nano zero-valent iron particles prepared by liquid phase reduction method is large.

[0006] Natural nano-mineral materials are one of the most widely used materials in the field of water environment remediation. Tourmaline is a typical natural nano-mineral material. Tourmaline acts as a catalyst in various chemical reactions such as redox reactions and synthesis reactions, which can effectively promote the reaction process and improve the purity of the product. Its unique physical and chemical properties make it have broad application prospects in industrial production and environmental protection. In the process of wastewater treatment, tourmaline can be used as a catalyst to promote the degradation and transformation of organic matter in wastewater, thereby reducing the content of pollutants in wastewater and achieving the purpose of purifying water quality. In order to further improve the activity of tourmaline, we used hydrogen reduction roasting tourmaline to obtain nanostructured tourmaline composite materials. Although its activity, surface energy and specific surface area have increased compared with unactivated tourmaline minerals, the nanostructured tourmaline composite material also has the phenomenon of easy agglomeration, which affects the active sites and reduces the efficiency of catalytic degradation of antibiotics. Therefore, it is urgent to develop highly active nano-mineral materials based on tourmaline.

[0007] Nanoconfined catalytic materials are materials that provide a "constrained" environment for catalytic reaction systems at the nanoscale. This material achieves precise control of the catalyst structure and performance through spatial or interfacial confinement effects, making the catalytic reaction more efficient and environmentally friendly. With the help of nanoscale spatial and interfacial confinement effects, the electronic energy state of the catalytic system is modulated. Nanoconfined catalytic materials play an important role in the treatment of antibiotic wastewater and other fields. Therefore, the preparation of nanomineral composite materials with nanoconfinement effects based on natural nanominerals is an effective means to solve the low catalytic efficiency of catalysts. Summary of the invention

[0008] In view of the problems existing in the above-mentioned prior art, the present invention provides a method for preparing a two-dimensional layered vermiculite mineral-based nano-confined material and its application in catalytic degradation of antibiotic pollutants to improve the catalytic reaction activity of the catalyst.

[0009] The method for preparing the two-dimensional layered vermiculite mineral-based nano-confined material of the present invention comprises the following steps:

[0010] Step 1: crushing vermiculite mineral, rhodochrosite mineral, tourmaline mineral, and sulfur mineral respectively and passing through a 200-mesh sieve to obtain vermiculite mineral powder, rhodochrosite mineral powder, tourmaline mineral powder, and sulfur mineral powder with a particle size of ≤0.075 mm;

[0011] Step 2: feeding the vermiculite mineral powder into a muffle furnace, and calcining it at 500-1000° C. for 2-5 hours in an air atmosphere to obtain expanded vermiculite mineral powder;

[0012] Step 3: Mix the expanded vermiculite mineral powder, rhodochrosite mineral powder and tourmaline mineral powder, evacuate and let stand for 12-24 hours, the vacuum degree range is 0.1Pa-10Pa, this process can accelerate the ion exchange of ions in rhodochrosite mineral and tourmaline mineral, and enter the interlayer domain in the expanded vermiculite mineral; then reduce and roast in a hydrogen atmosphere, the roasting temperature is 500-1000℃, the roasting time is 2-5 hours, and the vermiculite-based nano zero-valent composite material is obtained. The ions in tourmaline are Na, Ca, K, Mg, Fe, Mn, Li, Al, Si, B, O, H, F; the ions in rhodochrosite are Mn.

[0013] Step 4: Mix the vermiculite-based nano-zero-valent composite material with sulfur mineral powder, evacuate and let it stand for 12-24 hours, with a vacuum degree ranging from 0.1Pa to 10Pa, to accelerate the exchange of sulfur ions into the interlayer domain of the vermiculite-based nano-zero-valent composite material, and then place it in a high-pressure reactor under a nitrogen protective atmosphere, set the steam pressure in the high-pressure reactor to 0.1MPa-10MPa, and control the autoclave temperature to ≤300℃, so as to generate a two-dimensional layered vermiculite mineral-based nano-confined material in one step.

[0014] In step 3, the mass ratio of expanded vermiculite mineral powder, rhodochrosite mineral powder and tourmaline mineral powder is 5:1-4:1-2.

[0015] In step 4, the mass ratio of the vermiculite-based nano zero-valent composite material to the sulfur mineral powder is 1-5:1.

[0016] The specific surface area of ​​the two-dimensional layered vermiculite mineral-based nano-confined material of the present invention is 200-400m 2 / g.

[0017] The two-dimensional layered vermiculite mineral-based nano-confined material of the present invention is applied to the catalytic degradation of antibiotic pollutants and has high activity.

[0018] Specifically, two-dimensional layered vermiculite mineral-based nano-confined materials are added to wastewater containing antibiotic pollutants to catalyze the degradation of antibiotic pollutants.

[0019] In the catalytic degradation system, the concentration of antibiotics is 0.01 mg / L-5000 mg / L, the concentration of persulfate is 0.1 g / L-10 g / L, the addition amount of two-dimensional layered vermiculite mineral-based nano-confined material is 0.1 mg / L-10 g / L, the system pH is 2-12, and the temperature is room temperature.

[0020] The catalytic degradation time is 1-24h.

[0021] The wastewater containing antibiotic pollutants includes medical wastewater containing antibiotics.

[0022] The antibiotics include one or more of sulfamethoxazole, ofloxacin, enrofloxacin, tetracycline hydrochloride and norfloxacin.

[0023] The persulfate is peroxymonosulfate or peroxydisulfate.

[0024] In the raw materials of the present invention, the vermiculite mineral is a natural vermiculite mineral; the sulfur mineral is a natural sulfur mineral with a sulfur content of about 99%; the tourmaline mineral is a natural tourmaline mineral; and the rhodochrosite mineral is a natural rhodochrosite mineral.

[0025] The present invention uses vermiculite mineral, rhodochrosite mineral, tourmaline mineral and sulfur mineral as raw materials, prepares two-dimensional layered vermiculite mineral-based nano-confined mineral materials as catalysts, activates persulfate to catalyze and degrade antibiotics, and can effectively solve the problem of agglomeration of nano-mineral materials. In addition, sulfidation can improve the dispersion performance and enhance the stability of vermiculite-based nano-zero-valent composite materials, can effectively inhibit the hydrogen evolution process of nano-mineral materials, can improve the electronic selectivity of specific reactions, realize targeted catalytic degradation of antibiotics, and improve the efficient degradation efficiency of antibiotics. The catalyst is at the nanoscale, providing a constrained environment to the catalytic reaction system, thereby realizing the precise regulation of catalytic performance, improving the efficiency of the catalytic reaction, and solving the problem of low efficiency of catalytic degradation of antibiotics by currently available catalysts.

[0026] Vermiculite is a 2:1 type layered clay mineral with special structure and physicochemical properties. It is rich in resources, cheap and easy to obtain, and is an important nano mineral resource. Vermiculite is a two-dimensional layered clay mineral composed of magnesium (aluminum) oxygen octahedral sheets and silicon oxygen tetrahedral sheets. It has rich surface active groups. Its two-dimensional layered structure contains microscopic regions such as end faces, interlayer domains and siloxane surfaces. This special microstructure gives it high surface reactivity. There is a phenomenon of isomorphic substitution between its two-dimensional layers, which is manifested as a high charge density on the silicon oxygen tetrahedral sheet. The two-dimensional interlayer domain is filled with exchangeable hydrated cations, which can effectively balance the negative charge in the interlayer domain. The unique two-dimensional nano interlayer domain and a large number of surface active groups of vermiculite mineral make vermiculite mineral show good surface / interface reactivity. It can be used as a template for nano-confined materials to prepare mineral materials with nano-confined effects and be used in the treatment of antibiotic wastewater.

[0027] Sulfur is a tasteless and odorless non-metal. Pure sulfur is yellow crystals, also known as sulfur. Sulfur has many different valences, the most common ones are -2, 0, +4, +6, etc. Sulfur often appears in the form of sulfide or sulfate in nature, and pure sulfur also appears in volcanic areas. Previous studies have found that sulfur minerals will quickly oxidize to sulfate in aqueous solution, which can produce acid in situ and provide a suitable pH for advanced oxidation technology.

[0028] Rhodochrosite is a manganese carbonate mineral with a composition of Mn[CO3] and a trigonal crystal system. Previous studies have found that rhodochrosite has high thermochemical activity and produces a nano zero-valent manganese composite material after hydrogen reduction roasting. At the same time, its porosity and specific surface area become higher, which may make it a cheap and efficient catalyst for the degradation of antibiotic wastewater. The present invention is the first to use hydrogen reduction roasting to prepare a nano zero-valent manganese composite material.

[0029] Tourmaline is a common natural nano-mineral, belonging to the category of cyclic silicate minerals, often in the form of trigonal columnar crystals, containing elements such as Na, Ca, K, Mg, Fe, Mn, Li, Al, Si, B, O, H, and F. The surface thickness of tourmaline is about tens of microns, generating an electrostatic field of 104-107V / m. Under the action of the electrostatic field, water molecules undergo electrolysis to generate active molecules H3O + The strong interfacial activity makes tourmaline crystals have high catalytic performance. Its strong electric field effect makes OH in water - Increase, OH -O2 is easily generated when it gathers at the positive electrode of tourmaline, which increases the active oxygen in the aqueous solution. Its redox effect increases the degradation ability of antibiotics. In addition, tourmaline releases a variety of minerals and trace elements such as Na, Mg, Ca, K, Fe, Mn, Li, Al, Si, B, O, H, F, etc. in water, allowing water molecules to be mineralized.

[0030] Previous studies have found that the nanostructured tourmaline composite material obtained by hydrogen reduction roasting tourmaline has a pair of electric dipoles, and its surface thickness is more than ten microns. Within this range, there is a high electric field, one end produces a "positive electrode" and the other end produces a "negative electrode". Persulfate can accept electrons on the negative electrode surface of the nanostructured tourmaline composite material and give electrons on the positive electrode of the nanostructured tourmaline composite material. The infrared rays generated by the nanostructured tourmaline composite material can reduce the water molecule clusters and accelerate the ionization process of water. In addition, the dangling bonds on the surface of the nanostructured tourmaline composite material and the surface sites formed by transition metal ions provide active sites for the degradation of antibiotics, so that the antibiotics are enriched on the surface of the nanostructured tourmaline composite material, and the efficiency of catalytic degradation of antibiotics is improved.

[0031] The present invention is to anchor nanostructured tourmaline and nano zero-valent manganese in the interlayer domain of two-dimensional layered expanded vermiculite to prepare a composite mineral material with a nano-confined structure. The nano-confined space of the composite mineral material with a nano-confined structure can change the hydrogen bond network of water molecules, so that the nano-confined catalytic water phase exhibits abnormal dynamics, thermodynamics, and fluid mechanics properties and behaviors, controls the change in the number of hydrogen bonds of water molecules, and ultrafast fluid mechanics, and improves the catalytic degradation of antibiotics. In addition, crystal growth in the nano-confined space is prone to metastable output in the nucleation stage, exposure of dominant crystal faces in the growth stage, and other effects, through reversible regeneration of the crystal structure and multi-process partitioned crystallization. The nano-confined system can achieve efficient degradation of antibiotics under milder conditions by enriching antibiotics, stabilizing transition states, and changing the inner surface adsorption potential and redox state.

[0032] The present invention adopts two-dimensional layered vermiculite mineral-based nano-confined mineral materials to catalyze the degradation of antibiotics. The spontaneous electrical polarity of the two-dimensional layered vermiculite mineral-based nano-confined mineral materials is used to promote the decomposition of persulfate, generate hydroxyl radicals, sulfate radicals, and singlet oxygen, and catalyze the oxidation of antibiotics. The degradation rate of antibiotics in the treated water can reach 100%, and the intermediate products generated in the reaction process can also be finally degraded. The TOC removal rate reaches more than 70%, and the present invention is particularly suitable for wastewater containing difficult-to-degrade antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD diagram of vermiculite ore mineral.

[0034] Figure 2This is the XRD pattern of vermiculite mineral calcined at 200℃.

[0035] Figure 3 This is the XRD pattern of vermiculite mineral calcined at 300℃.

[0036] Figure 4 This is the XRD pattern of vermiculite mineral calcined at 400℃.

[0037] Figure 5 This is the XRD pattern of vermiculite mineral calcined at 500℃.

[0038] Figure 6 This is the XRD pattern of vermiculite mineral calcined at 600℃.

[0039] Figure 7 This is the XRD pattern of vermiculite mineral calcined at 700℃.

[0040] Figure 8 This is the XRD pattern of vermiculite mineral calcined at 800℃.

[0041] Fig. 9 This is the XRD pattern of vermiculite mineral calcined at 900℃.

[0042] Fig.10 This is the XRD pattern of vermiculite mineral calcined at 1000℃.

[0043] Figure 1-Figure 10 The XRD patterns of vermiculite minerals calcined at different temperatures (200-1000°C) are shown in Figure 2. Figure 1-Figure 10 It can be seen that within the range of 200-1000℃, the characteristic diffraction peak of vermiculite gradually increases with the increase of calcination temperature. This is because the high-temperature calcination of vermiculite minerals will lead to the loss of interlayer water and surface adsorbed water. When calcined from 30℃ to 200℃, vermiculite minerals begin to lose interlayer water and physically adsorbed water. The temperature range for the loss of structural hydroxyl groups is within the temperature range of 200-1000℃ ( Figure 1-Figure 10 ), the loss of hydroxyl groups in the octahedral sheet structure of vermiculite minerals leads to the destruction of the octahedral sheet structure of vermiculite minerals. When the calcination temperature increases from 800-1000℃, the two-dimensional layered vermiculite mineral structure disappears and forms new phases of three-dimensional structures such as mullite, cordierite, alumina and forsterite to form expanded vermiculite, which is a low-density layered mineral composite material. The Na + , Ca 2+ Mg 2+ and K + Ion dehydration forms a hydrated layered structure, and the interlayer water molecules of vermiculite minerals and Mg 2+Octahedral coordination is formed, and vacancies appear in the interlayer domain as different forms of water escape from the vermiculite mineral. In addition, the expanded vermiculite has open pores with a wide size distribution, and high-temperature heat treatment can significantly improve the effective exchangeability of ions, providing an effective template for the preparation of nano-confined composite materials.

[0044] Fig.11 AG in the figure are SEM images of tourmaline minerals at different magnifications. Fig.11 In the middle AF, we can see tourmaline, whose microstructure has a ring-shaped structure, a petal-shaped, and porous flake aggregate. Tourmaline has piezoelectricity and pyroelectricity, and is a polar crystal with a special structure that can generate ions. In the G figure with a higher magnification, we can see that tourmaline has nano-scale particles of nano-mineral materials.

[0045] Fig.12 The SEM images of tourmaline minerals calcined by hydrogen pyrolysis at 800°C are shown in Figure 1. AC is at different magnifications. The tourmaline minerals were calcined by reduction at 800°C in a hydrogen atmosphere for 4 hours to obtain a nanostructured tourmaline composite material. Fig.12 It can be seen that tourmaline is reduced and calcined under high temperature hydrogen to form a nanostructured pore structure, which has a large specific surface area and a nanopore structure.

[0046] Fig.13 Figure 1 is the SEM image of the original vermiculite mineral, and AD is different magnifications. Fig.13 It can be seen that the microstructure of the original vermiculite mineral has a porous structure, which is due to the nanopores formed in the vermiculite mineral during the geological process.

[0047] Fig.14 The SEM images of vermiculite mineral calcined at 400℃, AD are different magnifications. Fig.14 It can be seen that the microstructure of vermiculite mineral calcined at 400°C contains nanoparticles, but its structure is still dense and has a relatively low porosity.

[0048] Fig.15 The SEM images of vermiculite mineral calcined at 500℃, AD are different magnifications. Fig.15 It can be seen that the microstructure of vermiculite mineral calcined at 500°C contains nanoparticles, but its structure is still dense and has a relatively low porosity.

[0049] Fig.16 The SEM images of vermiculite mineral calcined at 600℃, AD are different magnifications. Fig.16 It can be seen that the vermiculite mineral calcined at 600°C has a layered microstructure. This is because the vermiculite mineral removes different forms of water during the calcination process, forming a porous layered sandwich microstructure.

[0050] Fig.17 The SEM images of vermiculite mineral calcined at 700℃, AD are different magnifications. Fig.17 It can be seen that the microstructure of the vermiculite mineral calcined at 700°C has layered structures and nanoparticles, which is because the vermiculite mineral is calcined and dehydrated at high temperature to form a nanostructured mineral composite material.

[0051] Fig.18 The SEM images of vermiculite mineral calcined at 800℃, AD are different magnifications. Fig.18 It can be seen that the vermiculite mineral calcined at 800℃ further forms a nano-layered sandwich microstructure. This is because the vermiculite mineral has good expansion properties when heated rapidly at high temperature, and the water molecules between the interlayer domain and the lamellae are quickly vaporized, and the interlayer domain is rapidly enlarged. In addition, the interlayer cations of the expanded vermiculite mineral are exchangeable. The special properties of the surface and interface structure of the expanded vermiculite mineral enable it to be used as a template for the preparation of nano-mineral confined materials, confining nanostructured tourmaline, nano zero-valent manganese, and sulfur in a limited space, thereby improving the catalytic reaction activity of the catalyst.

[0052] Fig.19 The SEM images of vermiculite mineral calcined at 900℃, AD are different magnifications. Fig.19 It can be seen that the microstructure of the vermiculite mineral calcined at 900°C has a layered structure morphology and nanoparticles, which is because the vermiculite mineral is calcined and dehydrated at high temperature to form a nanostructured mineral composite material.

[0053] Fig. 20 The SEM images of vermiculite mineral calcined at 1000℃, AD are different magnifications. Fig. 20 It can be seen that the microstructure of the vermiculite mineral calcined at 1000°C has a layered structure morphology and nanoparticles, which is because the vermiculite mineral is calcined and dehydrated at high temperature to form a nanostructured mineral composite material.

[0054] Fig.21 AE are SEM images of Example 1, and they are different magnifications. From AD, it can be seen that the two-dimensional layered vermiculite-based nano-confined mineral material has a porous nanostructure, and from the higher magnification E image, it can be seen that it has a nano-granular structural morphology.

[0055] Fig. 22 The following are the actual pictures of vermiculite mineral (A, B) and vermiculite mineral calcined at 700℃ (C, D). From A and B, we can see that the vermiculite ore particles are dense, and C and D are the expanded vermiculite calcined at 700℃, which has a lower density.

[0056] Fig.23 This is a model diagram of the crystal structure of vermiculite mineral. Fig.23It can be seen that the vermiculite mineral belongs to the monoclinic system. The crystal is composed of three basic structural layers stacked up. In each structural unit layer, the upper and lower basic layers are silicon-oxygen tetrahedrons, with their tips facing each other, and the middle is a silicon-hydrogen-magnesium-aluminum layer. In the structural unit layer, since part of the silicon is replaced by aluminum, there is excess negative charge, which is compensated by the cations between the structural unit layers. There is also a large amount of interlayer water in the structural unit layer, and the water molecules are distributed in layers. High-temperature calcination can expand the volume of vermiculite minerals and enhance the cation exchange capacity.

[0057] Fig.24 This is a crystal structure model diagram of tourmaline mineral. Tourmaline is a type of cyclic silicate mineral, and its general structural formula can be expressed as XY3Z6Si6O 18 (BO3)3W4, where X = Na + , Ca 2+ , K + , vacancy, Y=Mg 2+ , Fe 2+ , Mn 2+ 、AI 3+ , Fe 3+ , Mn 3 + , Li + , Z=AI 3+ , Fe 3+ Cr 3+ Mg 2+ , W=OH - 、F - , O 2- The different types of atoms or ions at the X, Y, and Z positions will affect the physical properties of tourmaline.

[0058] Fig.25 Schematic diagram of the preparation process of two-dimensional layered vermiculite-based nano-confined mineral materials. First, the expanded vermiculite mineral with a large interlayer domain is obtained by calcining the vermiculite mineral. Step A is the process of expanding vermiculite mineral, rhodochrosite mineral, and tourmaline mineral. The process is evacuated and left to stand for 24 hours, wherein the vacuum degree is 10Pa, so that iron, manganese, aluminum, sodium, magnesium, and lithium are anchored to the interlayer domain of the expanded vermiculite mineral through ion exchange, and then reduced and roasted in a hydrogen atmosphere to prepare a vermiculite nano-zero-valent composite material (step B). The vermiculite nano-zero-valent composite material is then mixed with sulfur powder (step C), evacuated and left to stand for 24 hours, wherein the vacuum degree is 10Pa, and under a nitrogen protective atmosphere, the steam pressure in the high-pressure reactor is 9MPa, and the temperature does not exceed 300°C to generate a two-dimensional layered vermiculite-based nano-confined mineral material in one step. DETAILED DESCRIPTION

[0059] The technical solution of the present invention is further analyzed and explained below through specific embodiments.

[0060] Embodiment 1:

[0061] The preparation method of the two-dimensional layered vermiculite mineral-based nano-confined material in this embodiment is as follows:

[0062] 1. First, the vermiculite mineral, rhodochrosite mineral, sulfur mineral and tourmaline mineral are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, rhodochrosite mineral powder, sulfur mineral powder and tourmaline mineral powder with a particle size of 0.075 mm respectively.

[0063] 2. First, calcine the vermiculite mineral powder in air at 700°C for 4 hours to obtain expanded vermiculite mineral material.

[0064] 3. Mix expanded vermiculite mineral material, rhodochrosite mineral powder and tourmaline mineral powder in a mass ratio of 2:1:1, evacuate and let stand for 12 hours at a vacuum degree of 1 Pa to accelerate the ion exchange of ions in tourmaline and rhodochrosite and enter the interlayer domain of the expanded vermiculite mineral; calcine the mixed mineral material at 700°C in a hydrogen atmosphere for 3 hours to obtain a vermiculite-based nano zero-valent composite material.

[0065] 4. Mix the vermiculite-based nano-zero-valent composite material and sulfur mineral powder in a mass ratio of 5:2, evacuate and let it stand for 12 hours with a vacuum degree of 1Pa to accelerate the entry of sulfur ions into the interlayer of the vermiculite-based nano-zero-valent composite material; place it in a high-pressure reactor under a nitrogen protective atmosphere, set the steam pressure in the high-pressure reactor to 5MPa, control the autoclave temperature to 250℃, and generate a two-dimensional layered vermiculite mineral-based nano-confined material in one step; its specific surface area is 206m 2 / g, the porosity is 74%, and the S content is 46%.

[0066] Embodiment 2:

[0067] The preparation method of the two-dimensional layered vermiculite mineral-based nano-confined material in this embodiment is as follows:

[0068] 1. First, the vermiculite mineral, rhodochrosite mineral, sulfur mineral and tourmaline mineral are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, rhodochrosite mineral powder, sulfur mineral powder and tourmaline mineral powder with a particle size of 0.075 mm respectively.

[0069] 2. First, calcine the vermiculite mineral powder in air at 800°C for 4 hours to obtain expanded vermiculite mineral material.

[0070] 3. Mix expanded vermiculite mineral material, rhodochrosite mineral powder and tourmaline mineral powder in a mass ratio of 5:1:1, evacuate and let stand for 15 hours with a vacuum degree of 3Pa to accelerate the ion exchange of ions in the tourmaline and enter the interlayer domain of the expanded vermiculite mineral; calcine the mixed mineral material at 800°C in a hydrogen atmosphere for 4 hours to obtain a vermiculite-based nano zero-valent composite material.

[0071] 4. Mix the vermiculite-based nanocomposite material and sulfur mineral powder in a mass ratio of 5:4, evacuate and let it stand for 15 hours with a vacuum degree of 3Pa to accelerate the entry of sulfur ions into the interlayer of the vermiculite-based nano zero-valent composite material; place it in a high-pressure reactor under a nitrogen protective atmosphere, set the steam pressure in the high-pressure reactor to 7MPa, control the autoclave temperature to 270℃, and generate a two-dimensional layered vermiculite mineral-based nano confined material in one step; its specific surface area is 261m 2 / g, the porosity is 68%, and the S content is 51%.

[0072] Embodiment 3:

[0073] The preparation method of the two-dimensional layered vermiculite mineral-based nano-confined material in this embodiment is as follows:

[0074] 1. First, the vermiculite mineral, rhodochrosite mineral, sulfur mineral and tourmaline mineral are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, rhodochrosite mineral powder, sulfur mineral powder and tourmaline mineral powder with a particle size of 0.075 mm respectively.

[0075] 2. First, calcine the vermiculite mineral powder in air at 900°C for 4 hours to obtain expanded vermiculite mineral material.

[0076] 3. Mix expanded vermiculite mineral material, rhodochrosite mineral powder and tourmaline mineral powder in a mass ratio of 5:3:1, evacuate and let stand for 18 hours with a vacuum degree of 5 Pa to accelerate the ion exchange of ions in the tourmaline and enter the interlayer domain of the expanded vermiculite mineral; calcine the mixture at 900°C in a hydrogen atmosphere for 4 hours to obtain a vermiculite-based nano zero-valent composite material.

[0077] 4. Mix the vermiculite-based nanocomposite material and sulfur mineral powder in a mass ratio of 5:1, evacuate and let it stand for 18 hours with a vacuum degree of 5Pa to accelerate the entry of sulfur ions into the interlayer of the vermiculite-based nano zero-valent composite material; place it in a high-pressure reactor under a nitrogen protective atmosphere, set the steam pressure in the high-pressure reactor to 9MPa, control the autoclave temperature to 280℃, and generate a two-dimensional layered vermiculite mineral-based nano confined material in one step; its specific surface area is 283m 2 / g, the porosity is 91%, and the S content is 71%.

[0078] Embodiment 4:

[0079] The preparation method of the two-dimensional layered vermiculite mineral-based nano-confined material in this embodiment is as follows:

[0080] 1. First, the vermiculite mineral, rhodochrosite mineral, sulfur mineral and tourmaline mineral are crushed through a 200-mesh sieve to obtain vermiculite mineral powder, rhodochrosite mineral powder, sulfur mineral powder and tourmaline mineral powder with a particle size of 0.075 mm respectively.

[0081] 2. First, the vermiculite mineral powder is calcined in air at 1000°C for 4 hours, and then vacuumed and left to stand for 24 hours with a vacuum degree of 10Pa to accelerate the ion exchange of ions in the tourmaline and enter the interlayer domain of the expanded vermiculite mineral; and the expanded vermiculite mineral material is obtained.

[0082] 3. Expanded vermiculite mineral material, rhodochrosite mineral powder and tourmaline mineral powder were mixed in a mass ratio of 5:4:2, and the mixture was calcined at 1000°C for 4 hours in a hydrogen atmosphere to obtain a vermiculite-based nanocomposite material.

[0083] 4. Mix the vermiculite-based nanocomposite material and sulfur mineral powder in a mass ratio of 7:2, evacuate and let it stand for 24 hours with a vacuum degree of 10Pa to accelerate the entry of sulfur ions into the interlayer of the vermiculite-based nano zero-valent composite material; place it in a high-pressure reactor under a nitrogen protective atmosphere, set the steam pressure in the high-pressure reactor to 10MPa, control the autoclave temperature to 105℃, and generate a two-dimensional layered vermiculite mineral-based nano confined material in one step; its specific surface area is 395m 2 / g, the porosity is 74%, and the S content is 61%.

[0084] Comparative Example:

[0085] 1. The vermiculite mineral was crushed through a 200-mesh sieve to obtain vermiculite mineral powder with a particle size of 0.075 mm; the vermiculite mineral powder was calcined at different temperatures (200-1000° C.) for 4 hours to obtain vermiculite minerals after different calcinations. The specific material samples are as follows:

[0086] Vermiculite raw mineral, vermiculite mineral calcined at 200℃-calcination time is 4 hours (200-vermiculite), vermiculite mineral calcined at 300℃-calcination time is 4 hours (300-vermiculite), vermiculite mineral calcined at 400℃-calcination time is 4 hours (400-vermiculite), vermiculite mineral calcined at 500℃-calcination time is 4 hours (500-vermiculite), vermiculite mineral calcined at 600℃-calcination time is 4 hours (500-vermiculite), The calcination time is 4 hours (600-vermiculite), the vermiculite mineral is calcined at 700℃ - the calcination time is 4 hours (700-vermiculite), the vermiculite mineral is calcined at 800℃ - the calcination time is 4 hours (800-vermiculite), the vermiculite mineral is calcined at 900℃ - the calcination time is 4 hours (900-vermiculite), and the vermiculite mineral is calcined at 1000℃ - the calcination time is 4 hours (1000-vermiculite).

[0087] 2. Crush the tourmaline mineral through a 200-mesh sieve to obtain tourmaline mineral powder with a particle size of 0.075 mm.

[0088] 3. The tourmaline mineral was crushed through a 200-mesh sieve to obtain a tourmaline mineral powder with a particle size of 0.075 mm; the tourmaline mineral powder was reduced and calcined in hydrogen at 800° C. for 4 hours to obtain a nanostructured tourmaline composite material.

[0089] 4. Reduce the iron salt to a nano zero-valent iron composite material in the liquid phase under sodium borohydride to obtain a nano zero-valent iron composite material. The specific surface area of ​​the composite material is 21m 2 / g.

[0090] 5. Mix the iron salt and the sulfur salt and reduce them in the presence of sodium borohydride to form a sulfide nano zero-valent iron composite material. The specific surface area of ​​the composite material is 27m 2 / g.

[0091] 6. Crushing the rhodochrosite through a 200-mesh sieve to obtain rhodochrosite powder with a particle size of 0.075 mm; the specific surface area of ​​the composite material is 13 m 2 / g.

[0092] 7. Crushing the rhodochrosite through a 200-mesh sieve to obtain rhodochrosite powder with a particle size of 0.075 mm; reducing and roasting the rhodochrosite powder in hydrogen at 800°C for 4 hours to obtain a nano zero-valent manganese composite material. The specific surface area of ​​the composite material is 34 m 2 / g.

[0093] 8. The preparation method of the two-dimensional layered vermiculite composite material is as follows:

[0094] (1) First, vermiculite mineral, rhodochrosite mineral, sulfur mineral, and tourmaline mineral are crushed and passed through a 200-mesh sieve to obtain vermiculite mineral powder, rhodochrosite mineral powder, sulfur mineral powder, and tourmaline mineral powder with a particle size of 0.075 mm, respectively.

[0095] (2) First, the vermiculite mineral powder is calcined at 900° C. in air for 4 hours to obtain expanded vermiculite mineral material.

[0096] (3) Expanded vermiculite mineral material, rhodochrosite mineral powder and tourmaline mineral powder are mixed in a mass ratio of 5:3:1, and the mixed mineral material is calcined at 900° C. for 4 hours in a hydrogen atmosphere to obtain a vermiculite-based nano zero-valent composite material.

[0097] (4) The vermiculite-based nanocomposite material and sulfur mineral powder were mixed in a mass ratio of 5:1, placed in a high-pressure reactor under a nitrogen atmosphere, the steam pressure in the high-pressure reactor was set to 9 MPa, and the autoclave temperature was controlled to 280 ° C, to generate a two-dimensional layered vermiculite composite material in one step; its specific surface area was 127 m 2 / g, the porosity is 32%, and the S content is 39%.

[0098] 9. The preparation method of vermiculite nanocomposite material is as follows:

[0099] (1) First, vermiculite mineral, sulfur mineral, rhodochrosite mineral, and tourmaline mineral are crushed and passed through a 200-mesh sieve to obtain vermiculite mineral powder, sulfur mineral powder, rhodochrosite mineral powder, and tourmaline mineral powder with a particle size of 0.075 mm, respectively.

[0100] (2) First, the vermiculite mineral powder is calcined at 900° C. in air for 4 hours to obtain expanded vermiculite mineral material.

[0101] (3) Expanded vermiculite mineral material, rhodochrosite mineral powder and tourmaline mineral powder were mixed in a mass ratio of 5:3:1, and the mixed mineral material was calcined at 900° C. for 4 hours in a nitrogen atmosphere to obtain a vermiculite-based nanocomposite material.

[0102] (4) The vermiculite-based nanocomposite material and sulfur mineral powder were mixed in a mass ratio of 5:1, placed in a high-pressure reactor under a nitrogen atmosphere, the steam pressure in the high-pressure reactor was set to 9 MPa, and the autoclave temperature was controlled to 280°C to generate a vermiculite nanocomposite material in one step; its specific surface area was 114 m 2 / g, the porosity is 37%, and the S content is 25%.

[0103] 10. The preparation method of vermiculite composite mineral material is as follows:

[0104] (1) First, vermiculite mineral, sulfur mineral, rhodochrosite mineral, and tourmaline mineral are crushed and passed through a 200-mesh sieve to obtain vermiculite mineral powder, rhodochrosite mineral powder, sulfur mineral powder, and tourmaline mineral powder with a particle size of 0.075 mm, respectively.

[0105] (2) First, the vermiculite mineral powder is calcined at 900° C. in air for 4 hours to obtain expanded vermiculite mineral material.

[0106] (3) Expanded vermiculite mineral material, rhodochrosite mineral powder and tourmaline mineral powder are mixed in a mass ratio of 5:3:1, and the mixed mineral material is calcined at 900° C. for 4 hours in an air atmosphere to obtain a vermiculite-based composite material.

[0107] (4) The vermiculite-based composite material and sulfur mineral powder were mixed in a mass ratio of 5:1, placed in a high-pressure reactor under an air protective atmosphere, the steam pressure in the high-pressure reactor was set to 9 MPa, and the autoclave temperature was controlled to 280°C to generate a vermiculite composite mineral material in one step; its specific surface area was 158 m 2 / g, the porosity is 15%, and the S content is 7%.

[0108] 11. The preparation method of biomass carbon-based sulfurized nano-mineral composite material is as follows:

[0109] (1) First, the straw, sulfur mineral, rhodochrosite mineral, and tourmaline mineral are crushed and passed through a 200-mesh sieve to obtain straw powder, rhodochrosite mineral powder, sulfur mineral powder, and tourmaline mineral powder with a particle size of 0.075 mm, respectively.

[0110] (2) Straw powder, rhodochrosite powder, sulfur powder and tourmaline powder were mixed in a mass ratio of 5:3:2:1, and the mixed mineral materials were calcined at 800°C for 4 hours in a nitrogen atmosphere to obtain a biomass carbon-based sulfurized nano-mineral composite material with a specific surface area of ​​93 m 2 / g, the porosity is 23%, and the S content is 13%.

[0111] Antibiotic Degradation Example:

[0112] The catalysts prepared in Examples 1-4 and Comparative Examples 1-11 were added to antibiotic medical wastewater at a dosage of 0.5 g / L, including sulfamethoxazole, ofloxacin, enrofloxacin, tetracycline hydrochloride and norfloxacin. The concentrations of the above antibiotics were all 100 mg / L, the concentration of sodium permonosulfate was 1 g / L, the catalytic reaction time was 8 hours, and the concentrations of the antibiotics before and after the reaction were monitored.

[0113] Table 1 and Table 2 are respectively the experimental data of the removal rate and mineralization rate of antibiotics in Examples 1-4. It can be seen from Table 1 and Table 2 that the degradation rate of antibiotics in Examples 1-4 is 100%, and the mineralization rate of antibiotics is greater than 70%, indicating that the two-dimensional layered vermiculite mineral-based nano-confined materials prepared in Examples 1-4 enhance the stability of reaction intermediates, promote electron transfer, and protect active centers. The interlayer intercalation grows nanostructured tourmaline, nano zero-valent manganese, and sulfur in the electric field of tourmaline itself drives ion intercalation nanosheets, and then is reduced between nanosheet layers. Restricting the behavior of atoms or clusters within the nanoscale range can effectively change the catalyst structure and electronic properties. It has a unique liquid microenvironment in a unique nano-confined space, which can stabilize reaction intermediates. The electron cloud density of the interlayer ion clusters is affected by lone pairs of electrons, which significantly improves the electron cloud density, improves the electron transfer efficiency, and thus improves the efficiency of its catalytic degradation of antibiotics.

[0114] It can be seen from Table 3 and Table 4 that the degradation rate and mineralization rate of antibiotics in Comparative Examples 1-11 are very low. Comparative Example 1 is a vermiculite mineral calcined in air at different temperatures to obtain expanded vermiculite at different temperatures, which has low activity and contains less transition metals, resulting in very low degradation rate and mineralization rate of antibiotics. Comparative Examples 2-7 are tourmaline minerals, nanostructured tourmaline composites, nano zero-valent iron composites, sulfide nano zero-valent iron composites, rhodochrosite, and nano zero-valent manganese composites. The degradation rate and mineralization rate of antibiotics are very low. This is because these nanostructured mineral materials have large surface energy and are very prone to agglomeration, which affects the catalytic degradation efficiency. Comparative Examples 8-10 are two-dimensional layered vermiculite composites, vermiculite nanocomposites, and vermiculite composite mineral materials. These composite materials have very low degradation rate and mineralization rate of antibiotics. This is because Comparative Examples 8-10 are composite materials prepared based on vermiculite, and no vacuum method is used for ion exchange. The composite materials prepared by these comparative examples do not have the nano-confinement effect, and the composite materials are very prone to agglomeration, resulting in inactivation, which affects the efficiency of catalytic degradation of antibiotics. Comparative Example 11 is a biomass carbon-based sulfide nano-mineral composite material, which has a very low degradation rate and mineralization rate for antibiotics. The biomass carbon-based sulfide nano-mineral composite material does not have the nano-confinement effect, which affects the efficiency of catalytic degradation of antibiotics.

[0115] Table 1 Example 1-4 Catalytic degradation of medical wastewater - removal rate of antibiotics (%)

[0116]

[0117]

[0118] Table 2 Mineralization rate of catalytic degradation of medical wastewater-antibiotics in Examples 1-4 (%)

[0119] Sulfamethoxazole Ofloxacin Enrofloxacin Tetracycline hydrochloride Norfloxacin Example 1 70 99 84 86 88 Example 2 80 93 88 89 85 Example 3 75 95 81 89 83 Example 4 81 97 83 91 86

[0120] Table 3 Comparative Examples 1-11 Catalytic degradation of medical wastewater-degradation rate of antibiotics (%)

[0121]

[0122]

[0123] Table 4 Comparative Examples 1-11 Catalytic Degradation of Medical Wastewater-Mineralization Rate of Antibiotics (%)

[0124]

Claims

1. A method for preparing a two-dimensional layered vermiculite mineral-based nano-confined material, characterized in that The steps include: Step 1: crushing vermiculite mineral, rhodochrosite mineral, tourmaline mineral and sulfur mineral respectively and passing through a 200-mesh sieve to obtain vermiculite mineral powder, rhodochrosite mineral powder, tourmaline mineral powder and sulfur mineral powder; Step 2: feeding the vermiculite mineral powder into a muffle furnace, and calcining it at 500-1000° C. for 2-5 hours in an air atmosphere to obtain expanded vermiculite mineral powder; Step 3: Mix the expanded vermiculite mineral powder, rhodochrosite mineral powder and tourmaline mineral powder, evacuate and let stand for 12-24 hours. This process can accelerate the ion exchange of ions in the rhodochrosite mineral and tourmaline mineral and enter the interlayer domain in the expanded vermiculite mineral; Then, the product is reduced and calcined in a hydrogen atmosphere to obtain a vermiculite-based nano zero-valent composite material; Step 4: Mix the vermiculite-based nano-zero-valent composite material with sulfur mineral powder, evacuate and let it stand for 12-24 hours to accelerate the exchange of sulfur ions into the interlayer domain of the vermiculite-based nano-zero-valent composite material, and then place it in a high-pressure reactor under a nitrogen protective atmosphere to react, thereby generating a two-dimensional layered vermiculite mineral-based nano-confined material in one step.

2. The preparation method according to claim 1, characterized in that: In step 3, the mass ratio of expanded vermiculite mineral powder, rhodochrosite mineral powder and tourmaline mineral powder is 5:1-4:1-2.

3. The preparation method according to claim 1, characterized in that: In step 3, the vacuum degree of the vacuum pump is 0.1Pa-10Pa.

4. The preparation method according to claim 1, characterized in that: In step 3, the calcination temperature of the reduction calcination in a hydrogen atmosphere is 500-1000° C., and the calcination time is 2-5 hours.

5. The preparation method according to claim 1, characterized in that: In step 4, the mass ratio of the vermiculite-based nano zero-valent composite material to the sulfur mineral powder is 1-5:

1.

6. The preparation method according to claim 1, characterized in that: In step 4, the vacuum degree of the vacuum pump is 0.1Pa-10Pa.

7. The preparation method according to claim 1, characterized in that: In step 4, when reacting in the autoclave, the steam pressure in the autoclave is set to 0.1 MPa-10 MPa, and the autoclave temperature is controlled to be ≤300°C.

8. Use of the two-dimensional layered vermiculite mineral-based nano-confined material prepared by any one of the preparation methods of claims 1 to 7 in catalytic degradation of antibiotic pollutants.

9. The use according to claim 8, characterized in that: The two-dimensional layered vermiculite mineral-based nano-confined material is added to wastewater containing antibiotic pollutants to catalyze the degradation of antibiotic pollutants. The wastewater containing antibiotic pollutants includes medical wastewater containing antibiotics, and the antibiotics include one or more of sulfamethoxazole, ofloxacin, enrofloxacin, tetracycline hydrochloride, and norfloxacin.

10. The use according to claim 8 or 9, characterized in that: In the catalytic degradation system, the concentration of antibiotics is 0.01 mg / L-5000 mg / L, the concentration of persulfate is 0.1 g / L-10 g / L, the addition amount of two-dimensional layered vermiculite mineral-based nano-confined material is 0.1 mg / L-10 g / L, the system pH is 2-12, and the temperature is room temperature.

Citation Information

Cited By

  • Tourmaline composite catalyst as well as preparation method and application thereof

    CN120381878A